Effect on serum potassium level in patients of diabetic nephropathy on spironolactone and ramipril over follow up period - Naresh, Ashish; Singh, Mahendra Pal; Giri, Richa (International Journal of Research in Medical Sciences, 2019)
Background: The study was conducted to evaluate the change in serum potassium level over follow up period in patients of diabetic nephropathy on spironolactone (25 mg) and ramipril (5 mg) and compare the results with diabetic nephropathy patients on Spironolactone (25 mg) alone. Methods: A comparative, prospective, non-randomized, non-blinded experimental study was conducted on 56 patients (30-70 yr.) of diagnosed type 2 diabetes mellitus showing proteinuria. Total duration of study was about one year from October 2017 to October 2018. Inclusion criteria followed in study were Age 30-70 years, diagnosed type 2 diabetes mellitus, serum potassium level <5 meq/l, estimated GFR >30 ml/min/1.73m2 and HbA1c <10%. Exclusion criteria were type 1 diabetes mellitus, impaired glucose tolerance secondary to endocrine disease, exocrine pancreatic disease, SBP >180 mmHg DBP >110 mmHg, UTI, hematuria, acute febrile illness, vigorous exercise, short-term pronounced hyperglycemia, obstructive uropathy, confirmed or suspected renal artery disease by USG doppler study, Serum potassium level >5.5 meq/l. Patients were divided in two groups, group A (n= 28, spironolactone 25 mg and ramipril 5 mg) and group B (n=27, spironolactone 25 mg). Subjects were followed over 12 weeks and baseline and 12-week serum potassium being compared. Other baseline base line laboratory investigation such as serum lipid profile, HbA1c, eGFR, fundus examination, ultrasonography (KUB), serum urea, serum creatinine, hemoglobin, were taken at the starting point. Results: Both the group after receiving respective drug were followed for 3-month duration and serum potassium level measured at end of 3 months. Mean values of baseline and follow up serum potassium for group A and group B were 4.24±0.59, 4.07±0.61 and 4.35±0.55, 4.16±0.61 respectively, p value found to be >0.05 at 95% CI. Conclusions: In the study it was concluded that p value found to be >0.05 at 95% C.I denoting that there is no significant difference between mean value of base line and follow up serum potassium value in both group. None of patients in either group had experienced hyperkalaemia over follow up period though serum potassium level were slightly higher in group A, but this difference was statistically not significant. Follow up period of study should be long enough to comment on safety profile of combining spironolactone and ACE inhibitors in diabetic nephropathy patients.